2018
DOI: 10.3390/children5040054
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Integrative Medicine in Residency Program: Relationship between Lifestyle Behaviors and Burnout and Wellbeing Measures in First-Year Residents

Abstract: It is widely recognized that burnout is prevalent in medical culture and begins early in training. Studies show pediatricians and pediatric trainees experience burnout rates comparable to other specialties. Newly developed Accreditation Council for Graduate Medical Education (ACGME) core competencies in professionalism and personal development recognize the unacceptably high resident burnout rates and present an important opportunity for programs to improve residents experience throughout training. These compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
0
16
0
4
Order By: Relevance
“…Several generous foundation grants (Lawlor Foundation and Mayday Foundation) have allowed for support of the faculty and research assistants. Notable scholarly work includes faculty collaboration with PIM thought leaders to produce an Academy of Pediatrics (AAP) position statement on pediatric integrative medicine [3] and detailed results from the Pediatric Integrative Medicine in Residency (PIMR) pilot program [46,121]. A recent study found immersive virtual reality safe and effective for treating complex regional pain syndrome [80,122].…”
Section: Integrative Medicine At Stanford Children’s Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Several generous foundation grants (Lawlor Foundation and Mayday Foundation) have allowed for support of the faculty and research assistants. Notable scholarly work includes faculty collaboration with PIM thought leaders to produce an Academy of Pediatrics (AAP) position statement on pediatric integrative medicine [3] and detailed results from the Pediatric Integrative Medicine in Residency (PIMR) pilot program [46,121]. A recent study found immersive virtual reality safe and effective for treating complex regional pain syndrome [80,122].…”
Section: Integrative Medicine At Stanford Children’s Healthmentioning
confidence: 99%
“…Trainee participation in this curriculum was a pivotal step towards formalizing PIM medical education efforts at Stanford Children’s. In addition to providing a foundation in PIM knowledge, the curriculum enabled residents to improve their own lifestyle and wellness behaviors during the pilot [121]. To supplement the online curriculum offered by PIMR, the faculty developed a pediatric integrative medicine and wellness elective for pediatric residents who wanted in-depth exposure to integrative medicine in practice.…”
Section: Integrative Medicine At Stanford Children’s Healthmentioning
confidence: 99%
“…In fact, estimates from the United States and European countries indicate that the prevalence of burnout may exceed 50% 3 . Resident physicians are especially vulnerable to burnout when they are new to their working environment and are exposed to pressure from senior colleagues 4 - 10 . In addition, physician burnout can increase the rate of medical errors, lead to suboptimal patient care, and reduce empathy.…”
Section: Introductionmentioning
confidence: 99%
“…The Pediatric Resident Burnout and Resilience Study Consortium is a collaboration of over 40 pediatric and medicine–pediatric training programs, with the aim of developing and studying best practices to prevent and mitigate burnout in pediatric residents . The University of Arizona Center for Integrative Medicine Pediatric Integrative Medicine in Residency includes a 100 hour self‐care curriculum that has been piloted at five pediatric residency programs and emphasizes approaches to a healthy lifestyle as well as concepts of pediatric integrative medicine …”
Section: Discussionmentioning
confidence: 99%